Evolution of Intron/Exon Structure of DEAD Helicase Family Genes in Arabidopsis, Caenorhabditis, and Drosophila - Boudet, Nathalie; Aubourg, Sébastien; Toffano-Nioche, Claire; Kreis, Martin; Lecharny, Alain

(untitled) (Genome Research, 2001)
The DEAD box RNA helicase (RH) proteins are homologs involved in diverse cellular functions in all of the organisms from prokaryotes to eukaryotes. Nevertheless, there is a lack of conservation in the splicing pattern in the 53 Arabidopsis thaliana (AtRHs), the 32 Caenorhabditis elegans (CeRHs) and the 29 Drosophila melanogaster (DmRHs) genes. Of the 153 different observed intron positions, 4 are conserved between AtRHs,CeRHs, and DmRHs, and one position is also found inRHs from yeast and human. Of the 27 different AtRHstructures with introns, 20 have at least one predicted ancient intron in the regions coding for the catalytic domain. In all of the organisms examined, we found at least one gene with most of its intron predicted to be ancient. In A. thaliana, the large diversity inRH structures suggests that duplications of the ancestralRH were followed by a high number of intron deletions and additions. The very high bias toward phase 0 introns is in favor of intron addition, preferentially in phase 0. Results from this comparative study of the same gene family in a plant and in two animals are discussed in terms of the general mechanisms of gene family evolution.